(untitled) (Research, Society and Development, 2022)
This article is part of a master’s-level research, linked to the Graduate Program in Science and Mathematics Teaching, at the Franciscana University, located in Santa Maria – Rio Grande do Sul. The investigation aimed to understand the challenges encountered by senior university professors, in the area of mathematics, in the construction of their professional identity, regarding the self-formation process. The research was developed through a qualitative approach, with Multiple Case Study based on Yin (2005). The theoretical framework that supported this research was Ferry (2004); Zabalza (2004); Cunha (2010); Marcelo (1999; 2009); Isaia (2006); Novoa (2009). The development of the research is based on the study of university professors with a long professional trajectory, who are based on the process of self-training, on rethinking pedagogical practice, on the context and on internal and external factors. It was concluded that the process of self-education, nowadays, is essential, given the dynamics of teaching work, in order to give new meaning to their practice in the classroom. The research resulted in the understanding that teachers are unique professionals, as they build their identity based on their views on their experiences and challenges.